Modeling metabolism in an integrated subtropical watershed-reservoir system - Tambara,Vinicius Teixeira (2017)
ABSTRACT Reservoirs are considered transition systems between rivers and lakes with particular features due to its morphology and watershed inflows. Studies about aquatic metabolism in subtropical aquatic ecosystems, particularly in reservoirs, have been based on direct measurements and statistical relationships in specific gauge stations of the system rather than on analytical models, which are capable of representing the metabolic processes at different temporal and spatial scales. This paper aimed to evaluate the temporal variability of metabolism in a subtropical reservoir, named Faxinal reservoir, located in Caxias do Sul, Rio Grande do Sul state, Brazil, by using an ecological model (IPH-ECO) which was coupled with a hydrological model (IPH-II) to estimate inflows and nutrient loadings from the watershed. After model calibration, metabolic daily rates of gross primary production (GPP) and respiration (R) were estimated over a 1-year period (from November 2011 to December 2012), considering a process-based algorithm based on dissolved-oxygen budget implemented in the IPH-ECO model. Faxinal reservoir were net heterotrophic 97% of the simulation period. The temporal variability of GPP and R followed the general pattern of phytoplankton biomass in reservoir, which was more related to autochthonous factors such as water residence time, light availability, nutrient concentration and zooplankton grazing. Only during heavy rainfall period, increasing the terrestrial exports, the concentration of phosphorus was higher leading to an increase of chlorophyll-a concentration and hence metabolic rates of GPP and R. Therefore, considering the long dry period during the simulation, the aquatic metabolism of Faxinal reservoir is more influenced by the internal dynamic of the aquatic ecosystem than the watershed inputs.